Financial impact on the adoption of software validation tasks in the analysis phase : a business case - Allasi Bardales, David Enrique (Pontificia Universidad Católica del Perú, 2017)
Some information systems in a group of kind of organizations (for example government administrative organizations) have a critical role so they must achieve requirements in a rigorous way. However, it is not a common practice to use validation tasks, so these requirements usually do not correspond to the need. This study aims to analyze the financial impact the adoption of practices related to validation in the phase of requirements management and analysis of software development. This study was carried out based on pre-test and post-test approach; in our case, we perform: first, an evaluation of a relevant and representative project; second, the organization introduces software validation tasks; and finally, an evaluation of an equivalence project with the improved process. We found that both project performed change during software life cycle. However, in the first one, the change was performed in the final stage, while the second project was made during the analysis stage. The requirements management and analysis process were improved and the results were observed during first stages and it represents a 16% of saved.
Keywords: Sistemas de información--Control de calidad.; Sistemas de información--Aspectos financieros; https://purl.org/pe-repo/ocde/ford#1.02.00